Successful replantation of 2 digits in a patient with thrombocytosis after splenectomy: A case report. Issue 22 (June 2018) - Hwang, Jae Ha; Kim, Dong Wan; Kim, Kwang Seog; Lee, Sam Yong
Abstract: Introduction: Thrombosis is the most common complication of thrombocytosis, which can be particularly damaging to reattached digits. We present a guideline about digital replantation when thrombocytosis is expected. Case presentation: We report a case of an 18-year-old man who sustained a traumatic amputation of two fingers and splenic rupture in a traffic accident. He underwent digital replantation the day after splenectomy when life-threatening conditions had been managed. The platelet count increased to over 1, 300, 000/mm 3 and post-splenectomy reactive thrombocytosis was diagnosed. Hydroxyurea and anagrelide were administered to control the platelet count after consultation with a hematologist. The reattached fingers survived without any complication. Conclusion: In patients with digital amputation, replantation can be attempted, even when thrombocytosis is expected, when requested by the patient. Furthermore, the platelet count should be actively controlled with medication to improve the survival rate of the reattached finger.